A Case for Economic Capital as a Pillar 1 Regulatory Tool. (6th March 2014) - Jacobs, Johann; van Vuuren, Gary
Abstract Regulatory capital – as a tool for financial regulation – has come under scrutiny following the financial crisis of 2007‐2010 in terms of its ability to achieve the major objectives of financial regulations, namely contributing to financial stability; the provision of equally competitive regulatory conditions for financial institutions; and aiming to ensure that regulatory capital requirements are risk‐sensitive. This article investigates and compares the risk‐sensitivity of economic capital and regulatory capital requirements empirically from a systemic and institution‐specific perspective. The results are assessed to determine whether current regulatory capital requirements are representative of the relevant risks financial institutions face. Given these results as well as calls to strengthen Basel's Pillar 2 disciplines in the aftermath of the crisis, it also presents a case for regulators to place a heavier reliance on economic capital – rather than regulatory capital numbers.